The socioeconomic conditions determining the development, persistence, and decline of forest garden systems - Belcher, B.; Michon, G.; Angelsen, A.; Ruíz Pérez, M.; Asbjornsen, H. (2005)
There is a range of forest management systems between pure extraction and plantation systems. Such ‘‘intermediate systems’’ range from wild forests modified for increased production of selected products to anthropogenic forests with a high-density of valuable species growing within a relatively diverse and complex structure. These systems, classed here as ‘‘Forest Garden Systems’’ (FGS), have important socioeconomic and ecological benefits, and yet they have been largely overlooked by researchers, development practitioners, and policy makers. Based on case examples and the authors’ experience, this paper analyzes the socioeconomic and institutional factors that explain the development, persistence, and decline of FGS. These systems combine productivity and biodiversity values and are important components in the diverse economic systems of their managers. As such, the model warrants increased attention to protect existing values, to support the adaptation of existing systems to changing circumstances, and to inform the development of new models of integrated forest management.